METHOD FOR OPTIMAL PLANNING MODEL-BASED ON FUZZY TRANSPORTATION PROBLEM - Skalozub, V. V.; Vietrova, O. V. (Science and Transport Progress, 2007)
In the article planning problems which use linear programming models with fuzzy coefficients and strict constraints are considered. Properties of solutions of such problems are defined and possible approaches to solving these problems are proposed. Also transportation problem in fuzzy formulation is considered. A method of reduction of transportation problem to models of above mentioned type is proposed together with solution algorithm.